SOME QUESTIONS REDRESS OF HARM CAUSED BY UNLAWFUL APPLICATION OF PREVENTION MEASURES TO SUSPECTED OR ACCUSED ON CRIMINAL CASE (Journal of actual problems of jurisprudence, 2019)
In given article the author considers some questions compensation of the harm caused by illegal application of a preventivepunishment suspected or accused on criminal case.